Sago and Rice are Ambiguous: Food Security Under the Food Hood of Development Discourse in Mentawai Islands - Erwin, Erwin; Irwandi, Ade (Lembaga penelitian dan pengabdian kepada Masyarakat, 2023)
This article discusses the food polemic that occurs in Mentawai due to development programs. Since the New Order era until now, development programs have enveloped the lives of Mentawai people, disrupting the balance, especially food security issues. Analysis from FSVA (Food Security and Vulnerability Map) shows that Mentawai Islands regency is the only area that experiences food insecurity in West Sumatra province. Through a descriptive approach and elaborating on the results of previous research, it shows the factors of development programs carried out by the government that are fatal to the food security of the Mentawai people, especially the transition from sago to rice. The result shows that the food security of Mentawai people is disrupted through the development process with the mission of 'modernizing' Mentawai people. Thus, making them far away and even switch from local food, namely sago, taro and banana sourced from the forest to rice. This is due to the government intervention through the 'resettlement program', social assistance, limited forest access and weak economic capabilities that put them under the pressure of development discourse and as if they need help. Whereas it is not what Mentawai people want and need. As a result, their access to food, which has been sourced from the forest, has been replaced by the rice paddy printing program. However, as an ethnic group that has a culture of gathering and hunting and farming, they do not have the ability to grow crops (agriculture). Therefore, the Mentawai people are still in the poverty line and the dilemma between eating sago or rice, both of which are not easy to obtain.